The Timing of Utterance Planning in Task-Oriented Dialogue: Evidence from a Novel List-Completion Paradigm - Barthel, Mathias; Sauppe, Sebastian; Levinson, Stephen C.; Meyer, Antje S. (Frontiers in Psychology, 2016)
In conversation, interlocutors rarely leave long gaps between turns, suggesting that next speak- ers begin to plan their turns while listening to the previous speaker. The present experiment used analyses of speech onset latencies and eye-movements in a task-oriented dialogue paradigm to investigate when speakers start planning their response. Adult German participants heard a confederate describe sets of objects in utterances that either ended in a noun (e.g. Ich habe eine Tür und ein Fahrrad (‘I have a door and a bicycle’)) or a verb form (Ich habe eine Tür und ein Fahrrad besorgt (‘I have gotten a door and a bicycle’)), while the presence or absence of the ﬁnal verb either was or was not predictable from the preceding sentence structure. In response, participants had to name any unnamed objects they could see in their own display in utterances such as Ich habe ein Ei (‘I have an egg’). The main question was when participants started to plan their response. The results are consistent with the view that speakers begin to plan their turn as soon as sufﬁcient information is available to do so, irrespective of further incoming words.